Lesbian, Gay, Bisexual and Trans Health Inequalities : International Perspectives in Social Work - Karban, Kate; Fish, Julie, 1955- (Book collections on Project MUSE., 2015)
Health inequalities have emerged as a key global concern in the early 21st century, revealing differences between individuals' health experiences or outcomes stemming from social inequalities, including sexual orientation and gender identity. Social workers play a key role in supporting LGBT people when their health is impaired, but they can also take action to actively promote health and well-being. This book will engage with social work's contribution to reducing LGBT health inequalities.